Age‐dependent mixture models for recovery data on animals marked at unknown age. Issue 1 (24th April 2012) - McCrea, Rachel S.; Morgan, Byron J. T.; Cole, Diana J.
<x xml:space="preserve">Abstract</x> Summary. Data are often collected from wild animals that have been marked at unknown age. As a result, standard probability models, fitted by maximum likelihood, cannot incorporate age dependence in probabilities of annual survival. We propose and fit new mixture models to ring–recovery data on birds ringed of unknown age, in which it is possible to incorporate age dependence in survival. It is shown that it is important to analyse simultaneously data on animals marked as young, and of known age, as otherwise the mixture model is parameter redundant. The potential of the approach is illustrated by a new analysis of data on mallards, Anas platyrhynchos, and the wider performance of the approach is demonstrated through simulation. The models provide a way of analysing correctly large numbers of historical data sets.